2013
DOI: 10.3402/tellusa.v65i0.18541
|View full text |Cite
|
Sign up to set email alerts
|

Potential of an ensemble Kalman smoother for stratospheric chemical-dynamical data assimilation

Abstract: A B S T R A C TA new stratospheric ensemble Kalman smoother (EnKS) system is introduced, and the potential of assimilating posterior stratospheric observations to better constrain the whole model state at analysis time is investigated. A set of idealised perfect-model Observation System Simulation Experiments (OSSE) assimilating synthetic limb-sounding temperature or ozone retrievals are performed with a chemistryÁclimate model. The impact during the analysis step is characterised in terms of the root mean squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However the linear dependence assumption between the MPs and OPs is likely to be challenged by the forecast model and/or by the observation operator which are highly non-linear. To a large extent, the 4DEnVar assimilation methods are very similar to the Ensemble Kalman Smoother (Evensen and van Leeuwen, 2000;Harlim and Hunt, 2007;Milewski and Bourqui, 2013). As the theoretical foundation for many 4DEnVar assimilation methods, the assumption of the linear dependence between the MPs and OPs has often been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…However the linear dependence assumption between the MPs and OPs is likely to be challenged by the forecast model and/or by the observation operator which are highly non-linear. To a large extent, the 4DEnVar assimilation methods are very similar to the Ensemble Kalman Smoother (Evensen and van Leeuwen, 2000;Harlim and Hunt, 2007;Milewski and Bourqui, 2013). As the theoretical foundation for many 4DEnVar assimilation methods, the assumption of the linear dependence between the MPs and OPs has often been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Like the above-mentioned method, it is apparent that a fixed-lag EnKS with lag N repeatedly corrects the dust emissions with observations from that time step up to N subsequent time steps. The EnKS solves an analysis equation very similar to that of EnKF but with time lags between the analysis and innovations (observations minus forecast) [20]. To efficiently assimilate the hourly aerosol observations from the next-generation geostationary satellite Himawari-8 [21], we apply a four-dimensional local ensemble transform Kalman filter (4D-LETKF) to solve the Kalman equations [22].…”
Section: Methodsmentioning
confidence: 99%
“…Using an ensemble Kalman filter and an intermediate-complexity model, Milewski and Bourqui [48] demonstrated that information about the ozone-wind cross-covariance is essential in constraining dynamical fields when ozone only is assimilated. Moreover they showed that a further reduction in error can be obtained with an ensemble Kalman smoother [49]. In a series of studies using 4D-Var and the ensemble Kalman filter, Allen et al [50][51][52] showed that poorly-specified observation error could lead to an increase in RMS wind error, that observational coverage is important such that wind extraction could be improved if several chemical tracers were used, and that the balance between wind and temperature could be offset by the wind recovery from tracer measurements.…”
Section: Introductionmentioning
confidence: 99%